Design and implementation of a new cable‐driven robot for MRI‐guided breast biopsy. Issue 2 (6th January 2020) - Liu, Wenxuan; Yang, Zhiyong; Jiang, Shan; Feng, Di; Zhang, Daguang
Abstract: Background: Breast cancer is one of the most common cancer diagnosed among US women. Early and accurate diagnosis using breast biopsy techniques is essential in detecting cancer. Methods: In this paper, we present a new cable‐driven robot for MRI‐guided breast biopsy. A compact three degree‐of‐freedom (DOF) semi‐automated robot driven by ultrasonic motors is designed with non‐magnetic materials. Next, a novel insertion trajectory planning algorithm based on the breast holder that we created is proposed and designed, which can help radiologists locate the lesion and calculate the insertion trajectory. To improve the accuracy of insertion, kinematic analysis and accuracy compensation methods are introduced. Results: An experimental study based on image recognition and positioning is performed to validate the performance of the new robot. The results show that the mean position accuracy is 0.7 ± 0.04 mm. Conclusions: Application of the new robot can improve breast biopsy accuracy and reduce surgery time.